Nevertheless, they persist: Cross-Country Differences in Homeownership Behavior - Stefanie Huber; Tobias Schmidt (Tinbergen Institute, 2022)
Cross-country differences in homeownership rates are large and persistent over time, with homeownership rates ranging from 44% in Switzerland to 83% in Spain. This paper investigates whether cultures-defined as behavioral attitudes passed across generations-may value homeownership differently, and could thus be a driving demand factor of the homeownership decision. To isolate the effect of cultural preferences regarding homeownership from the impact of other economic factors, we investigate second-generation immigrants' homeownership decisions in the United States between 1994 and 2017. Our findings indicate that cultural preferences for homeownership are persistent, transmitted between generations, and substantially influence the rent-versus-buy decision.
Keywords: G11; G40; R21; Z10; 330; Housing Markets; Homeownership Rates; Cross-Country Heterogeneity; Cultural Transmission; Household Housing decisions